A Solar Cell That Is Triggered by Sun and Rain. Issue 17 (21st March 2016) - Tang, Qunwei; Wang, Xiaopeng; Yang, Peizhi; He, Benlin
Abstract: All‐weather solar cells are promising in solving the energy crisis. A flexible solar cell is presented that is triggered by combining an electron‐enriched graphene electrode with a dye‐sensitized solar cell. The new solar cell can be excited by incident light on sunny days and raindrops on rainy days, yielding an optimal solar‐to‐electric conversion efficiency of 6.53 % under AM 1.5 irradiation and current over microamps as well as a voltage of hundreds of microvolts by simulated raindrops. The formation of π‐electron|cation electrical double‐layer pseudocapacitors at graphene/raindrop interface is contributable to current and voltage outputs at switchable charging–discharging process. The new concept can guide the design of advanced all‐weather solar cells. Abstract : A flexible solar cell that can be excited by sunlight and raindrops is presented. The solar‐to‐electric conversion efficiency is created by complicated photoelectrochemical reactions, while electric signals, produced by dropping raindrops on rGO film, arise from π‐electron|cation pseudocapacitance at the rGO/raindrop interface. This work could guide the design of all‐weather solar cells.